Investigation of the Physical Properties and Acoustic Performance of Composites Developed From Natural Fibres. Issue 4 (July 2022) - Krithika, S.M. Udaya; Mani, K.; Thangavelu, Sathish Kumar; Bharathi, C. Mohan; Saravanan, K.; Prakash, C.
Noise pollution is one of the most pressing issues in our society today. Controlling noise has become one of the most essential and prevalent factors in the development of acoustic materials. Traditionally, numerous expensive and synthetic sound-absorption materials, such as glass fibre, carbon fibre and polymer fibres were utilised to suppress noise, posing additional harm to living organisms and the environment. Natural fibres derived from renewable resources can be utilised as sound-absorption materials that are inexpensive, bio-degradable, recyclable and readily available. Natural fibre-reinforced composites are currently exclusively used for diverse applications in the automobile industry, construction, building sectors, furniture and other industries. The risk of physical harm and health issues has been greatly reduced by adopting these natural fibre materials. In this research, an attempt has been made to manufacture composites from four natural fibres: hemp, bagasse, Arenga pinnata and bamboo. These four natural fibres were mixed in a 50:50 proportion along with polypropylene and developed into a textile composite using the thermal bonding method. The developed natural composite materials were tested for sound-absorption co-efficient using the impedance tube method and various physical properties, such as flexural rigidity, thickness, tensile strength, elongation, areal density, air permeability and thermal conductivity, were analysed for the composites using the standard testing procedures. All the possible influential factors that determine the acoustic characteristics property of the fibres are taken into consideration for the enhancement of the acoustic absorption of the composites. The sound-absorption co-efficient percent of the Arenga pinnata /polypropylene composite sample is higher than other fibres.